(untitled) (CIPEEX, 2025)
According to a survey conducted by the Social Service of Industry (Sesi), 52% of Brazilians rarely or never engage in physical activities, while 22% exercise daily, 13% at least three times a week, and 8% at least twice a week. Based on this data, we are developing FITPLAN software, focused on the health and wellness sector, targeting amateur and professional athletes, gym-goers, personal trainers, and health professionals specializing in physical education. Our target audience includes both individuals who regularly engage in physical activity and those who do not, as well as those who maintain or do not maintain a balanced diet. The primary objective of this software is to improve people’s overall health by encouraging them to make better food choices and to engage in physical activity. We chose the agile Scrum framework because it aligns well with the software’s development context, and several key stages have already been reached, including the development of the software’s interfaces and graphical representations using UML and BPMN diagrams. FITPLAN aims to facilitate a healthier lifestyle for its users by providing an easy-to-use platform that combines diet planning and exercise routines, empowering individuals to take control of their well-being. We will use Scrum to ensure efficient development and the successful creation of the MVP.